The Effect of Barley and Lysine Supplementation on the longissimus lumborum Meat Quality of Pasture-Raised Fallow Deer (Dama dama) - Bureš, Daniel; Bartoň, Luděk; Kudrnáčová, Eva; Kotrba, Radim; Hoffman, Louwrens C (Foods (Basel, Switzerland), 2020)
The chemical characteristics (proximate composition, amino acids, and fatty acids) and sensory quality of the longissimus lumborum (LL) muscle of 45 farmed male fallow deer were investigated. The animals were divided into three separate groups (n = 15 per treatment): pasture-fed (P), pasture-fed and supplemented with barley (B), and pasture-fed and supplemented with barley and lysine (BL). Differences were observed in LL moisture and the intramuscular fat contents, the latter being almost two-fold greater in the meat of B and BL groups compared to P. The concentrations of histidine, leucine, alanine, glutamic acid and glycine in the raw meat were higher in the BL group compared to the P group. Higher contents of n-3 polyunsaturated fatty acids (PUFAs), and consequently lower n-3 ratios, were found in the P group, compared to the BL group. The grilled meat samples from the P group scored higher than the other groups for grassy flavour, and lower for liver flavour.
Keywords: amino acids; venison; nutrition; bucks; diets; sensory analysis